Corporate Social Responsibility in Response to COVID-19 in Industrial Companies in Ecuador - Véliz Valencia, Mercedes Noemi (2025)
The present study analyzed Corporate Social Responsibility (CSR) in the context of the COVID-19 pandemic, highlighting its importance as a strategy to address the economic, social, and environmental challenges arising from this global crisis. The objective was to identify the main actions and strategies implemented by Ecuadorian companies to ensure their sustainability and contribute to the well-being of their stakeholders. A bibliographic review methodology with a descriptive approach was employed, based on reliable secondary sources such as scientific articles, books, and reports obtained from recognized databases. The findings identified key measures adopted by companies, such as the implementation of health protocols, the strengthening of internal and external communication, and the reorganization of logistical and production processes. Furthermore, the role of international organizations like ISO 26000 and national entities such as the Ecuadorian Consortium for Corporate Social Responsibility (CERES) was highlighted, as they provided normative frameworks to guide responsible strategies. It was concluded that CSR not only enabled companies to respond to the immediate demands of the pandemic but also positioned them as key players in sustainable development by balancing economic profitability with social and environmental commitment and strengthening their resilience to future crises.